2021
DOI: 10.1111/jspn.12323
|View full text |Cite
|
Sign up to set email alerts
|

Youngsters' perceptions of the experience of pain and utilisation of over‐the‐counter pain medication as needed in community: A qualitative study

Abstract: Purpose Pain is common in youngsters. No matter its nature, youngsters' consideration of pain is complex since its communications vary as a function of several components. The aim of this study is to explore the youngsters' perception linked to their experience of physiological pain at the home/family setting, as well as their experience with the utilisation of over‐the‐counter pain medication as needed. Design and methods A qualitative exploratory study was undertaken with 22 youngsters aged 5–17 years old. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, this study has demonstrated that the role of siblings in the expression of pain by children does not seem to be considered by parents when they are evaluating their children's pain, as we did not find any verbatim evidence of such a topic from the parents interviewed. Yet interviews with youngsters aged 5-17 conducted by Ndengeyingoma et al (2021) showed that perceptions of pain tolerance and pain tolerance competition can occur among siblings. Hence, a child's modeling behavior of not only their parents but also of their siblings can interfere with the parent's interpretation of the child's pain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, this study has demonstrated that the role of siblings in the expression of pain by children does not seem to be considered by parents when they are evaluating their children's pain, as we did not find any verbatim evidence of such a topic from the parents interviewed. Yet interviews with youngsters aged 5-17 conducted by Ndengeyingoma et al (2021) showed that perceptions of pain tolerance and pain tolerance competition can occur among siblings. Hence, a child's modeling behavior of not only their parents but also of their siblings can interfere with the parent's interpretation of the child's pain.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is possible that these methods are not adapted to every situation. Parents who report relying on experience and testimony could partly explain why some parents tend to wait for the pain to get worse before administering analgesics to their child (Ndengeyingoma et al, 2021). In addition, parents reported that following nonpharmacological methods to relieve pain, they will often re-evaluate the intensity of the pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations